Вплив фільтраційних втрат води з регулюючих басейнів на прилеглі території - Орлінська, О. В.; Чушкіна, І. В.; Стрепетова, Х. В.; Orlinska, O. V.; Chushkina, I. V.; Strepetova, K. V. (Видавництво "Молодий вчений", 2019)
За результатами польових досліджень виявлені основні закономірності впливу тектонічного фактору на технічний стан сільськогосподарських гідротехнічних споруд (ГТС). Встановлюється наступна закономірність – чим більш тектонічно порушені райони, де розташовуються ГТС, тим більше зон фільтрації та обводнення в них. Для впливу тектонічного фактору детальних досліджень були вибрані два регулюючих басейна, які знаходяться в різних геологічних і гідрогеологічних умовах. Перший басейн Калинівської зрошувальної мережі Синельниківського району розташований в межах східної частини Українського щита(УЩ), другий РБ-6 Царичанської зрошувальної мережі в зоні переходу від УЩ до Дніпровсько-Донецької западини (ДДЗ). В першому випадку потужність осадових утворень незначна до 25 м, в другом складає 300 і більше метрів. Обидва райони приурочені до вузлів перетину крупних глибинних розломів.

Basing upon the results of field studies, key regularities of the effect of a tectonic factor upon tech-nical condition of agricultural hydrotechnical structures (HTS) have been identified. Following regularity has been determined – the more tectonically disturbed the areas are, the greater number of filtration zones (along with their watering) they demonstrate. All the retention basins and principal channels are located within the lineament zone of the northern-eastern strike specified on the basis of the interpreted satellite data; modern vertical and horizontal tectonic movements are associated to that zone as well. However, spatial location of a HTS relative to the fractured zones of different high orders, occurred within that lineament zone, is different. Two retention basins located within different geological and hydrogeological conditions have been selected to analyze in detail the effect of a tectonic factor. First one is the basin of Kalynivska irrigation network of Syn-elnykovo district; it is located within the eastern share of the Ukrainian shield (US); second basin is РБ-6 of Tsarychanka irrigation network within the transition from US to Dnipro-Donets Depression (DDD). In the first case, thickness of sedimentary formations is insignificant (up to 25 m); in the second case, it is 300 m and more. Both areas are associated to the nodes of intersection of large-scale deep faults. Fractured zones in the base-ment take on the role of natural drains within the zone of Kalynivska irrigation network; filtration water flows towards Sukha Kalyna ravine along that drains. Within this area, sedimentary cover is thin, and filtration water replenishes fracture water of the basement. On the contrary, in terms of Tsarychanka district, sediments are thick be-ing saturated with the filtration water. Within this territory, there are several water-bearing lev-els of temporary-water and ground-water types characterized by hydraulic connection. Thus, fracture rocks of the basement in terms of Tsarychanka district are located at the considerable depth; they do not act as natural drains for filtration water of the retention basin. Finally, it should be noted that the most significant effect of a tectonic factor upon HTS technical condition is expected within the main channels, which may be crossed repeatedly by fissured zones. Both geophysical and tectonic studies prove that consistent pattern.
Effect of water filtration losses from retention basins upon the neighbouring territories
Keywords: регулюючий басейн; фільтраційні витрати; метод природного імпульсного електромагнітного поля Землі; вертикальне електричне зондування; глибинні розломи; ґрунтові гідротехнічні споруди; моніторинг; аномалії; regulating pool; filtration charges; method of natural pulsed electromagnetic field of the earth; vertical electrical sensing; deep faults; ground hydro-technical structures; monitoring; anomalies